(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The US constitutional experience with regard to abortion rights provides a textbook example of the inability of constitutional adjudication to transcend the divisions of ordinary politics. This thesis is articulated through an examination of a series of aporias found in the reasoning of Dobbs regarding the existence of a constitutional right to abortion, the appropriateness of transcending Roe, and the role of constitutional adjudication in morally controversial cases. The lesson to be drawn from this jurisprudential involution is that constitutional adjudication should be neither heroic nor renouncing, but should, if anything, be modest: while the solution to social problems is primarily the responsibility of the legislature, the task of constitutional judges is setting the limits of tolerance against which legislative determinations must be measured.